Understanding Uterine Fibroids: Prevalence, Pathophysiology, and Management - Sadia, Haleema; Akram, Muhammad; Iftikhar, Momina; Umaru, Isaac John (Kwaghe International Journal of Sciences and Technology, 2025)
The most common type of benign uterine tumors are uterine fibroids, sometimes referred to as leiomyomas or myomas. Clinical indicators include infertility, obstetric problems, mass symptoms, pelvic tumors, pelvic discomfort, and irregular bleeding. Because of their symptoms, more than 30% of women with leiomyomas might look for therapy. Modern surgical options are based on the operation, although the method of therapy is influenced by the patient's age and desire to avoid "radical" surgery, such as a hysterectomy, or to retain fertility. Uterine fibroids' location, size, and number determine the course of treatment. In the pathogenetic process, fibroids are made up of smooth muscle, fibroblasts, and a significant amount of fibrous extracellular matrix. The shape, location, pathophysiology, and clinical symptoms of fibroids vary significantly. A woman's race can affect her likelihood of developing fibroids; Black women are more likely than White women to get fibroids earlier in life and to have more severe symptoms.